Orthodontic treatment needs: parents and child perception - Tashkandi, Nada; Al Sadoon, Mashael Abdullah; Albagshi, Jumana Mohammed; Bin Mandeel, Rana Mohammed; Albagshi, Thuraya Adnan (International Journal Of Community Medicine And Public Health, 2022)
Background: Malocclusion is one of the most common oral cavity malformations. It has a variety of effects on dental health, function, aesthetics, and psychosocial condition. The suggested treatment for such a condition is orthodontic treatment. This study aims to assess the perceptions of orthodontic treatment needs of parents and their children with relation to their perception in Riyadh, Saudi Arabia. Methods: This is a cross-sectional study that was conducted to study the perception of children and their parents about the need for orthodontic treatment. The data were collected at the pediatric clinics of Riyadh Elm university in Riyadh, Saudi Arabia, and included 379 parents and their school children aged 4-12 years. An interviewed questionnaire was used to collect the data from the children and their parents separately. Results: The study found that the perception towards the need for orthodontic treatment of children and their parents was 44.6%, and 34.8% respectively. Also, a statistically significant difference was shown between the perception of children and their parents (p>0.05). The main factors affecting the perception was age, as the desire to have orthodontic treatment increased among children above age of 10 years. Other factors including satisfaction about chewing, teeth appearance, and social media altered the perception for orthodontic treatment need. Conclusions: These findings could be essential for orthodontic treatment planning and increasing patient compliance. The difference between children and parents’ perceptions can affect drive toward initial orthodontic visit.